COMPREHENSIVE METHODOLOGY FOR INVESTIGATION OF MIDDLE FRACTIONS OF PETROLEUM (World Science, 2021)
A methodology has been developed for separation and identification of hydrocarbons of middle 250-350°C fractions of Taribani and Mirzaani petroleum (Georgia) in order to determine their individual hydrocarbon composition. The middle fractions of petroleum are difficult to study objects due to the huge variety of hydrocarbon isomers present in them.The methodology includes the following complex of physical and chemical methods for processing of petroleum: distillation, dearomatization by adsorption chromatography, thorough separation of isoalkanes from cycloalkanes using three stages thermal diffusion, processing of the obtained concentrates with thiocarbamide. To determine the individual composition of the fractions, instrumental methods of gasliquid chromatography analysis on capillary columns, MS and GC/MS were used. The developed methodology has been successfully applied to the separation of paraffinic, isoparaffinic and cycloparaffinic hydrocarbons and to determine molecular composition of the middle fractions. Separation of isomers from the concentrates obtained by way of thermal diffusion fractions of Taribani and Mirzaani petroleum was achieved and a number of isoprenoids of C11-C23 composition were identified, in thiocarbamide concentrates there were polycyclic alkanes of C11-C16 composition, and in filtrates - relict, polymethyl-substituted decalins of C14-C16 composition